Teacher Factors and Academic Performance of Multigrade Pupils in Baybay City Division: Inputs to an Improved Implementation of Multigrade Teaching - Ruiz, Josemilo (JPAIR Institutional Research, 2020)
The study determines the relationship between the selected teacher factors and the academic performance of multigrade pupils in the Baybay City Division. The selected teacher factors were the socio-demographic profile variable (age, sex, civil status, educational qualification, teaching experience, teaching position, and training attended) and teacher empowerment dimensions (decision making, professional growth, status, self-efficacy, autonomy, and impact). The respondents of this study were the multigrade teachers, heads of the multigrade teachers, and the multigrade pupils in the division. The study used descriptive correlation employing a triangulation design. Descriptive statistics, chi-square test, Pearson r correlation, analysis of variance (ANOVA), and regression were used. The teaching profession consistently attracts women to its fold, making it a woman’s world. The same profession is staffed by a relatively young group of female teachers who were 40 years old and below and are expected to be in their productive and reproductive years as most of them are married. Multigrade teachers need uplifting in their educational qualifications, training, and similar initiatives to raise their rank, morale, motivation, and competence to remain in teaching. The extent of teacher empowerment dimensions with respect to decision making, professional growth, status, self-efficacy, autonomy, and impact are very highly empowered. The very poor academic showed in the five (5) learning areas is a brazen demonstration of a need to seriously evaluate multigrade instruction in the division. Among the selected teacher factors, only sex and professional growth turned out to be predictors of academic achievement in selected learning areas.